Preparation of activated carbon from date pits using mechanical milling method / Noor Syafiqah Mohd Ridzuan - Mohd Ridzuan, Noor Syafiqah (2025)
The growing demand for sustainable and cost-effective adsorbents has spurred research into alternative carbon sources for environmental applications. This study examines the preparation of activated carbon from date pits using the mechanical milling method. Chosen for their high carbon content and potential for value-added utilization, date pits are an abundant agricultural by-product. The activation process involved mechanical milling to reduce particle size, followed by thermal treatment to enhance porosity and surface area. The resulting activated carbon was characterized through scanning imaging to assess its textural and morphological properties. The findings show that mechanical milling effectively reduces particle size and increases surface area, thereby enhancing the adsorption potential of the produced activated carbon. This study demonstrates the feasibility of utilizing date pits as a sustainable precursor for activated carbon production, promoting waste valorization and environmental sustainability.